v-Myb Mediates Cooperation of a Cell-Specific Enhancer with the mim-1 Promoter - Chayka, Olesya (American Society for Microbiology, 2005)
The oncogenic transcription factor v-Myb disrupts myelomonocytic differentiation and transforms myelomonocytic cells by deregulating the expression of specific target genes. One of these genes, the chicken mim-1 gene, is activated by Myb exclusively in myelomonocytic cells and, therefore, has been an interesting model system to study how Myb activates a target in a lineage-specific manner. Previous work has suggested that Myb activates mim-1 by cooperating with CCAAT box/enhancer binding protein beta (C/EBPβ) or other C/EBP transcription factors at the mim-1 promoter. We have now identified and characterized a powerful Myb-dependent enhancer located 2 kb upstream of the mim-1 promoter. The enhancer is preferentially active in myelomonocytic cells, confers Myb responsiveness onto a heterologous promoter, and dramatically increases Myb responsiveness of the mim-1 promoter. Chromatin immunoprecipitation demonstrates that v-Myb and C/EBPβ are bound to the enhancer in v-Myb-transformed cells; furthermore, cooperation of the enhancer with the mim-1 promoter is greatly stimulated by C/EBPβ and p300. Taken together, our results show that the regulation of mim-1 expression by v-Myb is more complex than previously assumed and involves two distinct regions of the mim-1 gene. A major function of v-Myb (in addition to its role at the mim-1 promoter) apparently is to activate the mim-1 enhancer and, together with C/EBPβ and p300, facilitate its cooperation with the promoter. Interestingly, our work also shows that the v-Myb protein encoded by avian myeloblastosis virus is defective in this function, suggesting an explanation for why primary avian myeloblastosis virus-transformed myeloblasts do not express the mim-1 gene.